Transactions on Computational Science XXI Special Issue on Innovations in Nature-Inspired Computing and Applications - Gavrilova, Marina L.; Tan, C. J. Kenneth; Abraham, Ajith; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This, the 21st issue of the Transactions on Computational Science journal, edited by Ajith Abraham, is devoted to the topic of nature-inspired computing and applications. The 15 full papers included in the volume focus on the topics of neurocomputing, evolutionary algorithms, swarm intelligence, artificial immune systems, membrane computing, computing with words, artificial life and hybrid approaches.
Community Optimization -- Diffusion of Innovation Simulation Using an Evolutionary Algorithm -- Driving Robots Using Emotions -- Land Cover Feature Extraction of Multi-spectral Satellite Images Based on Extended Species Abundance Model of Biogeography -- Developing Issues for Ant Colony System Based Approach for Scheduling Problems -- Multiobjective Optimization of Green Sand Mould System Using Chaotic Differential Evolution -- Categorical Feature Reduction Using Multi Objective Genetic Algorithm in Cluster Analysis -- Tuning Meta-Heuristics Using Multi-agent Learning in a Scheduling System -- Vertical Transfer Algorithm for the School Bus Routing Problem -- An Efficient Craziness Based Particle Swarm Optimization Technique for Optimal IIR Filter Design -- Effect of Spatial Structure on the Evolution of Cooperation in the N-Choice Iterated Prisoner$1 (Bs Dilemma -- Extracting, Identifying and Visualisation of the Content, Users and Authors in Software Projects -- Beehive Based Machine to Give Snapshot of the Ongoing Stories on the Web -- Incorporating Highly Explorative Methods to Improve the Performance of Variable Neighborhood Search -- Self Organising Maps on Compute Unified Device Architecture for the Performance Monitoring of Emergency Call-Taking Centre.s
Keywords: Computer science; Information theory; Electronic data processing; Data mining; Artificial intelligence; Engineering; Computer Science; Theory of Computation; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Numeric Computing